Supporting the next generation of non-communicable disease research leaders in Africa – experience of the GSK Africa NCD Open Lab. (2020) - Addo, Juliet; Strange, Mike; Kendall, Lindsay; Stylianou, Annie; Gatsi, Sally; Guta, Phyllis; Scott, Rhona; Ako, Agbor
No abstract available